2021
DOI: 10.3390/nano11092208
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofiber-Based Viroblock/ZnO/PAN Hybrid Antiviral Nanocomposite for Personal Protective Applications

Abstract: Designing novel antiviral personal protective equipment (PPE) is crucial for preventing viral infections such as COVID-19 in humans. Here, we fabricate an electrospun nanofiber-based Viroblock (VB)-loaded polyacrylonitrile (PAN)/zinc oxide (ZnO) hybrid nanocomposite for PPE applications. Five different concentrations of Viroblock (0.5%, 1.5%, 2.5%, 3.5%, and 5%) were added to PAN/ZnO solution and loaded for electrospinning. The developed samples reflected antibacterial activity of 92.59% and 88.64% against Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…However, it should be noted that some studies have indicated a high toxicity of ZnO-NPs to human cells at relatively high concentrations and low particle sizes [69]. Indeed, ZnO has shown properties against intestinal diseases by protecting intestinal cells from Escherichia coli infection by inhibiting bacterial adhesion and internalization [70].…”
Section: Antibacterial and Fungal Analysismentioning
confidence: 99%
“…However, it should be noted that some studies have indicated a high toxicity of ZnO-NPs to human cells at relatively high concentrations and low particle sizes [69]. Indeed, ZnO has shown properties against intestinal diseases by protecting intestinal cells from Escherichia coli infection by inhibiting bacterial adhesion and internalization [70].…”
Section: Antibacterial and Fungal Analysismentioning
confidence: 99%
“…In 1983, William has pointed that the membrane filter technology can be used for the separations of particles, bacteria, viruses, macromolecules and ions ranging from 0.1 to 10 μm in liquids [166] . With the rapid growth of market demand, membranes especially the nanofiber membranes have been widely used in textiles industry due to their porous structure and large surface to volume ratio, which can both filter particles and absorb chemical contaminants [167] , [168] , [169] , [170] , [171] . From 2019 to present, these products effectively prevent the plague transmission of COVID-19 which have posed a severe threat to human life.…”
Section: Membranes For Medical Supportmentioning
confidence: 99%
“…Inorganic nanoparticles exhibit antioxidative behavior, such as cerium oxide nanoparticles 4,[8][9][10][11] and zinc oxide (ZnO) nanostructures. [12][13][14][15][16] ZnO is an economical option for this application because it is not a rare earth oxide, which helps in cost and availability. As such, ZnO is the material we are investigating in the current work.…”
Section: Introductionmentioning
confidence: 99%